PNPLA3, TM6SF2, and MBOAT7 Influence on Nutraceutical Therapy Response for Non-alcoholic Fatty Liver Disease: A Randomized Controlled Trial - Dallio, Marcello; Masarone, Mario; Romeo, Mario; Tuccillo, Concetta; Morisco, Filomena; Persico, Marcello; Loguercio, Carmelina; Federico, Alessandro (Frontiers in Medicine, 2021)
Introduction PNPLA3, TM6SF2 and MBOAT7 genes play a crucial role in non-alcoholic fatty liver disease (NAFLD) development and worsening, however few data are available on their treatment response influence. The aim of this trial was to explore the effect derived from silybin-phospholipids complex (303 mg of silybin-phospholipids complex, 10 mg of vitamin D, and 15 mg of vitamin E twice a day for six months) oral administration in NAFLD patients carrying PNPLA3-rs738409, TM6SF2-rs58542926, MBOAT7-rs641738 genetic variants. Materials and methods Ninety-two biopsy proven NAFLD patients were grouped in 30 NAFLD wild type controls, 30 wild type treated patients and 32 mutated treated ones. We assessed glycemia (FPG), insulinemia, HOMA-IR, aspartate and alanine aminotransferases (AST, ALT), C-reactive protein (CRP), thiobarbituric acid reactive substance (TBARS), stiffness, controlled attenuation parameter (CAP), dietary daily intake, physical activity at baseline and end of treatment. Results The wild-type treated group showed a significant improvement of FPG, insulinemia, HOMA-IR, ALT, CRP, TBARS (p<0.05), whereas no improvements were recorded in the other two study groups. NAFLD wild-type treated patients showed higher possibilities of useful therapeutic outcome (p<0.01), obtained from the prescribed therapeutic regimen, independently from age, sex, comorbidities, medications, CAP and stiffness in comparison to the mutated group. Discussion The assessed mutations are independently associated with no response to a silybin-based therapeutic regimen and could be considered as useful predictive markers in this context.